Insulin resistance, C-reactive protein, diastolic to systolic blood pressure ratio and epicardial fat are related to sedentary time, and inversely related to physical activity in school-aged children - Vasileva, Fidanka; Carreras-Badosa, Gemma; Bassols, Judit; Serrano-Ferrer, Juan; Font-Lladó, Raquel; López-Ros, Victor; Osiniri, Inés; Martínez-Calcerrada, Jose-Maria; San Millán, Marta; López-Bermejo, Abel; Prats-Puig, Anna (Frontiers in Public Health, 2024)
Background Physical activity (PA) is beneficial for the overall health. Objectives are: (1) To compare metabolic (MRM) and cardiovascular-risk-markers (CRM) in children according to their PA-level; (2) to explore the associations of MRM and CRM with PA and sedentary time (ST); and (3) to identify the associations between MRM and CRM in less (LA) and more active (MA) children. Methods A total of 238 apparently healthy school-aged children were enrolled (132 boys/106 girls; 9.1 ± 1.8 years) and body mass index standard deviation score (BMI SDS) and blood pressure were assessed. Fasting venous blood sampling was performed to assess insulin resistance (HOMA-IR) and high-sensitivity-C-reactive protein (hsCRP). Epicardial fat, interventricular septal and left ventricular posterior wall thicknesses were assessed by high-resolution ultrasonography. PA and ST were assessed by enKid-questionnaire. Children were classified based on enKid-score as being LA and MA (below and above 50th percentile for PA). Results MA-children had lower values for: BMI SDS, diastolic-to-systolic blood pressure ratio, HOMA-IR and hsCRP (7.02 to 61.5% lower, p = 0.040 to p < 0.0001) compared to LA-children. MRM and CRM were positively associated with ST (p = 0.003 to p < 0.001), and negatively associated with PA (p = 0.044 to p < 0.001). Finally, MRM were positively associated with CRM (p = 0.008 to p < 0.0001). Interestingly, the latter associations were observed in LA-children but were not present in MA-children. Conclusion More PA is associated with better cardio-metabolic profile in school-aged children. PA seems to modulate the associations between MRM and CRM, thus reinforcing the idea that fostering PA in children may lower the risk for development of a cardio-metabolic disease.